Simulation of BNNSs Dielectrophoretic Motion under a Nanosecond Pulsed Electric Field - Yan Mi; Xin Ge; Jinyan Dai; Yong Chen; Yakui Zhu (Nanomaterials, 2021)
Using a nanosecond pulsed electric field to induce orientation and arrangement of insulating flake particles is a novel efficient strategy, but the specific mechanism remains unclear. In this study, the dielectrophoretic motion of boron nitride nanosheets (BNNSs) in ultrapure water under a nanosecond pulsed electric field is simulated for the first time. First, the simulation theory is proposed. When the relaxation polarization time of the dielectric is much shorter than the pulse voltage width, the pulse voltage high level can be considered a short-term DC voltage. On this basis, the Arbitrary Lagrangian–Euler (ALE) method is used in the model, considering the mutual ultrapure water–BNNS particles-nanosecond pulsed electric field dielectrophoretic interaction, to study the influence of different BNNSs self-angle α and relative angle β on local orientation and global arrangement. The particles are moved by the dielectrophoretic force during the pulse voltage high level and move with the ultrapure water flow at the zero level, without their movement direction changing during this period, so the orientation angle and distance changes show step-like and wave-like curves, respectively. The model explains the basic mechanism of dielectrophoretic motion of BNNSs under a pulsed electric field and summarizes the motion law of BNNSs, providing a reference for subsequent research.